PENGARUH DOSIS PUPUK ORGANIK SUPER K TERHADAP WAKTU MUNCUL BUNGA DAN PRODUKSI TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) - Sanjungi firman Irwanda; Syafrinal; M. Amrul Khoiri (DINAMIKA PERTANIAN, 2025)
This study aims to evaluate the effects of super K organic fertilizer application on the flowering phases, yield components, and the relationships among observed variables of oil palm (Elaeis guineensis Jacq.), as well as to determine the fertilizer dose that provides the best response in yield components. The study was conducted over six months, from March to September 2024. The experiment was arranged in a Completely Randomized Design (CRD) with four levels of super K organic fertilizer application, namely K1 = 3 kg plant⁻¹, K2 = 4 kg plant⁻¹, K3 = 5 kg plant⁻¹, and K4 = 6 kg plant⁻¹. Each treatment was replicated five times, yielding 20 experimental units. Each experimental unit consisted of two sample plants, for a total of 40. The collected data were analyzed using analysis of variance (ANOVA) and further tested using Duncan’s New Multiple Range Test (DNMRT) at the 5% significance level. The results showed that super K organic fertilizer application had no significant effect on the time to spathe emergence, time to flower emergence, time to female flower receptivity, time to male flower anthesis, sex ratio, and the number of fresh fruit bunches harvested per plant. However, super K organic fertilizer significantly affected the fruit maturation period and fresh fruit bunch weight per plant, with the 5 kg plant⁻¹ dose providing the best performance. Correlation analysis revealed strong to powerful relationships among several flowering variables and oil palm yield components.